Analysis of construction on elastic foundation with evaluation of all system dead weight/Konstrukcijų ant tampraus pagrindo skaičiavimas įvertinant visos sistemos savąjį svorį - Grigusevičius, Andrius; Kalanta, Stanislovas; Krutinis, Antanas (Journal of Civil Engineering and Management, 2001)
Solution of constructions on an elastic foundation was formulated as the contact problem [1], [2]. With such a formulation the stress and strain state is investigated at the contact of construction and foundation. Therefore, we can not evaluate the influence of elastic foundation dead weight for stress and strain distribution in the soil. The aim of this article is to solve this pressing problem, which allows to define in more precise way the stress and strain state in the system, and to evaluate not only the dead weight of the construction, but also the dead weight of foundation. The system “construction-substructure-foundation” is investigated as an interaction of separate bodies. Such a formulation allows to go over from solving contact problems to the solution of qualitatively new problems in which the distribution of stresses and strains in foundation along the depth is evaluated. Mathematical models in this article are realised by computer programme COSMOS/M. The stress-strain state is determined by describing the system “wall-substructure-foundation” of elements with different physical-mechanical indices. Article in Lithuanian. First Published Online: 30 Jul 2012